Balanced Score Card (BSC) dan Kembalian Pendidikan - Ade Ahmad Mubarok; Wiwi Uswatiyah; Iim Wasiman; Uyun Supyan (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
This study aims to analyze the balanced score card model in realizing quality schools, starting from strategies, implementation roadmaps, to measuring the success of quality schools. The research method used is an exploratory study to formulate the BSC concept in high school quality management. As a result, the strategy to improve the quality of education in high school starts from the formulation of the school's vision and mission, analysis of the internal and external environment with a SWOT analysis approach and BSC-based which produces information strengths, weaknesses, opportunities, and threats for high school. SMA targets and strategies are implemented properly so that the high school targets are in accordance with the vision and mission and the established strategies have been implemented properly according to the needs of the community. To ensure sustainable quality, the formulation of strategic management needs to be adapted to the dynamics of the development of the internal and external environment of the school concerned..